Fundamentals of Programming for Science and Engineering - Maxville, Valerie (SE4Science 2018 : 2018 ACM/IEEE International Workshop on Software Engineering for Science : proceedings : 2 June 2018, Gothenburg, Sweden, 2018)
It is common for science and engineering courses to include one computing unit, usually in first year. In a newly-developed first-year unit, we have combined Python coding, Science and Engineering applications and research-oriented skills to help students understand how coding may be applied in their studies and research. Student responses have been positive, and the unit continues to evolve in response to student and faculty feedback. With increasing uptake in the unit, it is hoped that a wave of computational literacy will foster an increase in the application of computational techniques by undergraduate and postgraduate students.